Peningkatan Branding UMKM Rental ATV dalam Mendukung Ekowisata Berkelanjutan di Pantai Air Manis - Riyan Ogilvi; Sonya Tri Amelia; Rahmat Rezky; Faradika (CV. ITTC INDONESIA, 2025)
Air Manis Beach in West Sumatra is one of the region's leading tourist destinations, offering significant potential for development through sustainable ecotourism approaches. One of the popular tourist activities in the area is ATV (All-Terrain Vehicle) rental operated by Micro, Small, and Medium Enterprises (MSMEs). However, the branding of these ATV rental MSMEs remains suboptimal, limiting their ability to enhance tourist experiences and strengthen local identity. This study aims to formulate strategies for improving MSME branding to support sustainable ecotourism in the area. A qualitative approach was used, involving observations, in-depth interviews, and document analysis. The findings indicate that improving service quality, establishing a consistent visual identity, implementing digital promotion with local storytelling, and fostering collaboration with tourism communities and local governments are key factors in strengthening MSME branding. A strong branding strategy not only increases business competitiveness but also contributes to environmental conservation and local community empowerment as integral aspects of sustainable ecotourism practices